Business Model Innovation of Indonesian Integrated Wood Depot For Furniture Industry - Adhitya Rahmana; Yudha Heryawan Asnawi; Afdhal; Aswin Fajri (Jurnal Manajemen & Agribisnis, 2021)
The wood-based industry is faced with various problems, both internal and external, especially the problem of availability and continuity of raw materials. The study aims to analyses the business model that has been implemented by this wood depot. Then, this study also analyses the feasibility based on the business model innovation of this wood depot initiative. This research uses an analytical framework of the Business Model Canvas (BMC) and Financial Feasibility Canvas (FFC). The Business Model Canvas presents a visual representation of the nine components of a business which are divided into the right (creative side) and left (logic side) on one page. The analysis uses the Financial Feasibility Canvas (FFC) which consists of 6 steps of analysis components consisting of rational investment, capital investments, assumptions, cash flows, financial returns, and decisions. The results of this study show that this business model innovation at this integrated wood depot can strengthen the speed of supply of raw materials and can maintain continuity to the furniture industry. The sustainability of this business model innovation is realized through vertical integration into the furniture industry. Based on the feasibility analysis, this business model has a feasibility in terms of investment for 5 years. In the future, the wood depot in this business model can be applied to industry players in Indonesia. Keywords: wood depot, financial feasibility canvas, wood-based industry, business model innovation, business strategy